Step-by-step explanation:
1st
8x-59 + 2x-11 = 180
10x -70 = 180
10x = 180 + 70
10x = 250
x = 25
2nd
8x - 59 = 15y + 6
8(25) -59 = 15y + 6
200 -59 = 15y + 6
141 = 15y + 6
15y + 6 = 141
15y = 141 - 6
15y = 135
y = 135/15
y = 9
Answer: 17x+9
Step-by-step explanation:
Step-by-step explanation:
secants originating from the same point have the same relative length relationship :
outside part × sum of outside and inside parts
is the same for every secant from the same point.
so,
5×(7+5) = 6×(2x-8+6) = 12x - 12
60 = 12x - 12
12x = 72
x = 6
WV = 2x - 8 = 2×6 - 8 = 12 - 8 = 4
so, B is correct.
Answer:
C is a constant ( a value that doesn't change)
Step-by-step explanation:
for example (X^2), here x is a variable with an exponent. (8x), here 8 is a coefficient. making c a constant.